DETECTION OF LINGUAL FORAMINA IN THE MANDIBULAR INTERFORAMINAL REGION USING LIMITED CONE BEAM COMPUTED TOMOGRAPHY - Andrei Leonid Chirita; Teodora Matei; Mihai Predoiu (Romanian Society of Oral Rehabilitation, 2020)
Purpose: The interforaminal area, traditionally considered a relatively safe area for dental implants, is investigated in this study using limited cone beam computed tomography (CBCT) to evaluate the frequency and localization of lingual foramina that may transmit arterial branches and pose a hemorrhagic life-threatening risk. Method: A retrospective study was conducted on 33 limited CBCT patient scans to evaluate the frequency and localization of lingual foramina. Additionally, the course and anastomosing pattern of the bony canals originating in these foramina were evaluated. Results: All of the patients (100%) showed lingual foramina. Of the 152 lingual foramina found, 64 were median lingual foramina (MLF) and 88 were lateral lingual foramina (LLF). Continuity with the mandibular incisive canal (MIC) was seen in 31.8% (n=28) of the LLC. Conclusion: Lingual foramina are frequently present in the anterior mandible and should be localized prior to surgical intervention in this area.